Combined effects of deficit irrigation and mulching on fruit quality and bioactive compounds of VNR Bihi guava (Psidium guajava) - JAT, RAJKUMAR; SINGH, V P; DWIVEDI, SHAILENDRA KUMAR; SINGH, OMVEER; RAI, RATNA; KUMAR, RAJESH; CHOUDHARY, ASHOK; ARJOO (The Indian Journal of Agricultural Sciences, 2024)
The present study was carried out during 2019–20 and 2020–21 at Govind Ballabh Pant University of Agriculture and Technology, Pantnagar, Uttarakhand to assess the combined effects of deficit irrigation and mulching on a 5-year- old VNR Bihi guava (Psidium guajava L.) orchard. The experiment consisted of three irrigation regimes, viz. deficit irrigation at 50% ETc (DI50); deficit irrigation at 75% ETc (DI75); and full irrigation at 100% ETc (FI100); and four mulching treatments, viz. silver-black mulch (MSB); black mulch (MB); organic mulch (MOM); and without mulch (MWM) laid out in a factorial randomised block design (F-RBD) with three replications. Results showed that fruit number and yield/tree were recorded highest in trees irrigated with DI75 and mulched with silver-black mulch. Under treatment DI50 fruit had the highest concentration of soluble solids, with Brix levels of 12.35°B and 12.78 °B during the years 2019–20 and 2020–21, respectively. Total sugars content was significantly increased under DI50 by 7.73 and 7.36%, respectively as compared to FI100 during both the years of experimentation. The biochemical properties such as total phenolics, total flavonoids and antioxidant (DPPH) activity also increased as irrigation regimes decreased from FI100 to DI50. The total phenolic and flavonoids content were improved by 19.19 and 33.44%, respectively under DI50 when compared to FI100. Significant differences among different mulch treatments with respect to quality parameters were also observed except DPPH activity. Silver-black mulch followed by black mulch resulted in higher soluble solids content, total sugars, ascorbic acid, total phenolic content, total flavonoids and DPPH activity. These findings demonstrate the positive effect of water deficit practice on bioactive compounds and the appropriateness of deficit irrigation and mulching as irrigation management strategies in the fruit orchards that improve fruit commercial value and conserve water.